Effect of garlic (Allium sativum) - supplemented diet on growth performance, body composition and fatty acid profile of rainbow trout (Oncorhynchus mykiss) - ÖZ, Mustafa; DİKEL, Suat (Cellular and Molecular Biology, 2022)
In this study, rainbow trout were fed for a total of 90 days with different feed mixes containing 0.00%, 1.00%, 1.50% and 2.00% garlic (Allium sativum). The effect of garlic on the growth performance, body composition and fatty acid profile of rainbow trout was researched. The starting weight of fish in the experimental group was approximately 64.12±0.29 gr, which increased to 234.12±3.54gr, 246.31±4.41gr, 258.74±4.42gr, and 268.79±4.79gr, while the difference in growth between the groups was observed to be statistically significant (p<0.05). At the end of the feeding period, the specific growth rate (SGR), the economic conversion ratio (ECR), the feed conversion ratio (FCR), the economic profit index (EPI) and the protein efficiency ratio (PER) were checked. In this study, the nutritional composition and fatty acid profiles of fish after 90 days of feeding were examined. As a result of this study, the supplementation of garlic to the diet given to rainbow trout caused an increase in their protein ratio and a decrease in their moisture content and fat ratio. Additionally, it led to a decrease in fatty acid and monounsaturated fatty acid levels and an increase in polyunsaturated fatty acids.